Межличностное пространство и взаимопонимание – основа здорового образа жизни [Articol] - Анцибор, Людмила; Сырбу, Анна (CEP USM, 2013)
În articoleste abordat subiectul cu privire la direcţiile de dezvoltare a sănătăţii, în special la esenţa acesteia, care trebuie corelată cu problema esenţei şi naturii umane. Realitatea existenţei umane, fiind o caracteristică centrală ce formează esenţa conţinutală a persoanei, este legată de modalităţile de interacţiunea acesteia cu alte persoane şi cu lumea, în general. Componenta psihică integrală (generală) a sănătăţii este cea mai sensibilă şi, totodată, cea mai flexibilă pentru toate acţiunile lumii sociale şi se formează sub influenţa lor nemijlocită. Trăsăturile caracteristice persoanei se formează şi se autocreează prin intermediul unui mecanism special constituit în societate, şi anume – relaţiile interpersonale. Relaţiile persoanei cu realitatea înconjurătoare sunt determinate de orientările valorice şi înţelegerea reciprocă, de capacitatea de a tolera deosebirile dintre persoane, de simţul apartenenţei şi de sentimentul de satisfacţie.

This article is describing directions, and the main purpose of the heal th’s development, which needs a correlation with the problem of the human nature and essence. Mental component of the integral (total) health is the most sensitive and at the same time, the most flexible to all the impacts of the social world and it’s formed under its direct influence. Personal characteristics of a human are forming and self-creating, and need some special "mechanism", which is the society, and a special "tool" -interpersonal relationships. The reality of human entity, that is, the central semantic characteristics of a human being as of a personality, is tied with its way of relating to another person, to the whole world. Relationship between the personality and the surrounding reality are defined by values and orientations, understanding (intimate, confessional communication), the ability to be tolerant to the differences between people, belonging, awe and gratitude. The most characteristic treats of a mature, healthy personality are realistic ambitions, attention to the course of its self-realization, the struggle for the space of its personal development, etc.
INTERPESONAL SPACE AND MUTUAL UNTERSTANDING – THE MAIN PECULIARITIES OF A HEALTHY WAY OF LIFE
Keywords: stil de viaţă sănătos; calitatea vieţii; înţelegere reciprocă; healthy life style; personal integrity; understanding